THE DEVELOPMENT OF EXERCISE PROGRAM WITH FAMILY INVOLVEMENT ON SELF STIMULATING BEHAVIOR OF STUDENT WITH AUTISTIC - Laemdeeklam, Sasima; Pornma, Kitikorn; Sriyeethong, Chutima; Pongthong, Warisara; Lertsuwan, Kanthika; Khemake, Aunthika (Life Sciences and Environment Journal, 2025)
This study aimed to (1) develop an exercise program with family participation to reduce self-stimulatory behaviors in children with autism, and (2) evaluate the effects of the program after implementation. The sample consisted of 46 parents of children with autism. The instruments used in this research were: (1) a parent satisfaction questionnaire, and (2) a structured behavioral observation form. Descriptive statistics including frequency, percentage, and mean were used, along with inferential statistics such as independent samples t-test and one-way ANOVA. Results showed high parental satisfaction and a notable reduction in self-stimulatory behaviors in children after participation. Families reported ease in applying the program at home. No significant difference in satisfaction was found between male and female parents, but a significant difference was found among different age groups. The study recommends improving clarity of the program and developing user-friendly materials to support long-term behavioral outcomes.